Penyuluhan Kesehatan Asuhan Komplementer untuk Mengurangi Ketidaknyamanan Fisiologis Kehamilan di Puskesmas Kalasan Sleman Yogyakarta - Wahyuni, Kenik Sri; Mindarsih, Eko; Wahyuningsih, Melania; Olvianda, Olvianda (Jurnal Pengabdian UNDIKMA, 2024)
This service aims to increase pregnant women's knowledge and skills regarding complementary care, which is useful for reducing physiological discomfort during pregnancy. The targets of this service were pregnant women who had complaints of physiological discomfort during pregnancy, especially pregnant women in the second and 3rd trimesters. The method of implementing this service used participatory action, including observation, Focus Group Discussion (FGD), counseling and training. Program evaluation used a questionnaire with descriptive data analysis to assess the knowledge and skills of pregnant women before and after the intervention. The results of the service showed that the characteristics of pregnant women were that most of them are of healthy reproductive age (20 - 35 years), were in their second pregnancy, were in their second trimester of pregnancy, have secondary education and work as private employees. After education and training, there was an increase in knowledge of 37.04% and an increase in skills of 25.92% regarding complementary care during pregnancy. It showed that the outreach and training programs implemented positively contribute and impact in the implementation of complementary pregnancy care to reduce physiological discomfort during pregnancy.